The Darjeeling Limited - Yeoman, Robert D. 1951-; Brody, Adrien 1972-; Schwartzman, Jason 1980-; Wilson, Owen 1968-; Murray, Bill 1950-; Huston, Anjelica 1951- (The Criterion collection, 2010)
Three American brothers set off on a train voyage across India to find themselves and bond with each other. They find themselves stranded alone in the middle of a desert and a new unplanned journey begins